Placebo effect of carbohydrate feedings during a 40-km cycling time trial - Clark, V. R.; Hopkins, W. G.; Hawley, J. A.; Burke, L. M. (Medicine & Science in Sports & Exercise, 2000)
Purpose: The placebo effect, a favorable outcome from belief that one has received a beneficial treatment, may be an important phenomenon in athletic performance. We have therefore investigated the placebo effect of a carbohydrate supplement on endurance performance. Methods: Forty-three competitive endurance cyclists (2 female, 41 male) performed two simulated 40-km time trials on an air-braked ergometer. In the first trial they ingested water to establish baseline performance (mean power 265 ± 46 W for 58 ± 4 min, mean ± SD). For the second trial 6-8 d later they were randomized to two groups: one group ingested 16 mL·kg-1 of a drink containing 7.6 g·100 mL-1 carbohydrate; the other ingested an indistinguishable noncaloric placebo drink. Cyclists in each group were further randomized to three subgroups according to whether they were told the drink contained carbohydrate, placebo, or either (not told). Results: Changes in mean power in the second trial were: told carbohydrate, 4.3 ± 4.8%; told placebo, 0.5 ± 5.8%; and not told, -1.1 ± 8.5%. The difference between the told-carbohydrate and told-placebo groups was 3.8% (95% likely range 7.9 to -0.2%). The change in performance in the not-told group was more variable than that of the told groups by a factor of 1.6 (2.6 to 1.0). The real effect of carbohydrate was a slight reduction in power of 0.3% (4.4 to -3.8%). Conclusions: (a) The placebo effect of a potentially ergogenic treatment during unblinded laboratory time trials lasting ~1 h is probably a small but worthwhile increase in endurance power. (b) Blinding subjects to the treatment increases individual differences in endurance effort, which may reduce precision of performance outcomes in controlled trials.